IMPACT OF MIGRATION ON THE BRAZILIAN FORMAL LABOR MARKET (REMUNOM, 2025)
The study investigates the impact of migration on the Brazilian formal labor market between 2012 and 2022, analyzing the evolution of migrant participation and its regional distribution. The research uses data from SISMIGRA and RAIS to evaluate trends and patterns of migrant workers’ insertion, combining descriptive and inferential analysis through linear and log-linear regression models. The results indicate a continuous growth in the proportion of formally employed migrants, with an average annual percentage increase of 9.4%. However, the distribution of migrants in the formal labor market is not homogeneous across states, being more significant in São Paulo, Santa Catarina, and Paraná, while Roraima and Amazonas register intense migration flows but face challenges in integrating migrants into formal employment. The literature demonstrates that migration can contribute to the economy but encounters structural barriers such as discrimination and occupational segmentation. The study concludes that public policies for inclusion and professional qualification are essential to promote migrant integration and ensure their sustainable participation in the formal labor market, maximizing the economic and social benefits of migration for Brazil.